L’introuvable capitale du Mali. La question de la capitale dans l’historiographie du royaume médiéval du Mali - Hadrien Collet (Afriques)
In the writings of “colonialist historians”, the hypothesis of Niani was certainly the main one formulated about the capital of medieval Mali at its height, from the 13th till the middle of the 15th century. This hypothesis, produced by colonial history in 1923 but partially deconstructed since the 1970s, still has strong support despite its outdated approach to writing history. It was advanced during the colonial era and the period of independence (the 1960s), before being subjected to a critique from academic history and archaeology. The historiography of Niani is presented as a reflection of trends in the writing of the history of the ancient Sudan, and current research on Mali’s capital is examined.